Self-care practice of individuals suffering from diabetes - Rahmah, Mohd Amin; Myat Moe, Thwe Aung; San San, Oo (2019)
Diabetes mellitus is a worldwide problem and it is increasing dramatically. It is considered one of the main leading causes of death around the world. It is highly associated with morbidity and mortality. However, the prevalence of diabetes mellitus is predicted to rise in the future with increased risk factors that include urbanization, obesity, and a sedentary life style. This global prevalence of diabetes makes all health care institutions incompetent with patients’ dayto-day needs. The main focus in treating diabetes including: healthy diet regimen; taking medication; glucose check monitoring; solving problems, fluctuation glucose level; minimizing risks; activity tolerance; and psychosocial adaptation. There are many factors which impact the diabetes self-care practice and quality of life must be taken into consideration that include: sociodemographics factors, social support, psychosocial adaptation, marital status, availability of insurance, duration of diabetes, morbidities, family support, foot care, smoking cessation, cultural and spiritual issues. This paper reviews these factors and shows that there is a noticeable negative or positive impact on glycemic control for diabetic patients. It recommended for more attention to be given and to schedule a holistic regimen for treating diabetes practices mellitus.